Typology and Morphology of Traditional Sasak Settlement - Grace Friscilia Thane (University of Merdeka Malang, 2024)
The cultural richness that characterizes Sasak is reflected in the form of architecture, landscape patterns, and settlements. It is known that there are six traditional villages, each of which has a share in the enrichment of Sasak culture and beauty. The architectural objects taken are from traditional villages on Lombok Island inhabited by the Sasak Tribe by exploring the historical and socio-cultural significance to explain their unique characteristics and the influence of history and cultural beliefs on settlement patterns. This research focuses on physically grouping settlement patterns and relating them to culture and local regulations to find the typology and morphology of traditional Sasak settlements. These two classifications are influenced by history and the phenomenon of the 2018 earthquake in these settlements, highlighting the resilience and cultural significance of traditional Sasak structures. Key findings include the classification of two forms of Sasak architecture settlement patterns: hilly Sasak architecture and flat land Sasak architecture., each with distinct characteristics and orientations. The study provides valuable insights into the architectural, historical, and cultural aspects of traditional Sasak settlements, contributing to a deeper understanding of their significance and unique characteristics.